Labor Market Signaling and Unemployment Duration: Evidence from Germany - Sebastian Becker; Elke Jahn (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
The aim of the paper is to examine the consequences of displacement on unemployment duration. Due to ex-ante asymmetric information about the productivity of unemployed applicants, prospective employers use the type of displacement as a costless signal about the ability of the worker when making hiring decisions. While individual layoffs might be caused by workers low productivity, plant closures can be considered as exogenous. Consequently, individual layoffs might attach a negative productivity signal to the worker resulting in longer unemployment duration. To test this hypothesis we use administrative linked employer-employee data for Germany which not only contain daily information on unemployment duration but also allows us to control for the type of displacement. We show that workers displaced due to plant closures and downsizings find indeed significantly faster a new job. We also find the strengths of the signaling value to be proportional to the share of displaced workers.
Keywords: J64; J65; J68; 330